Popular knowledge about medicinal plants: a study with rural families (Research, Society and Development, 2021)
Plants with medical properties have been used as a therapeutic resource since ancient ages, and this practice currently represents one of the main interventions inself-care in the population. The goal of this study is to assess the knowledge of rural families about the use of medicinal plants in health care. It consists of a qualitative, exploratory and descriptive study performed with twenty families living in the rural area of a city located in the Northwest region of the Rio Grande do Sul State. Data collection was performed through semi-structured questions, and data analysis was carried out through thematic analysis. The project was approved by a Research Ethics Committee under number 2.628.655. Results reveal that the participants use medicinal plants mostly for digestive and respiratory symptoms, for relief of inflammation, and as anxiolytics. Their knowledge concerning plant species comes mainly from previous generations, but also from neighbors and the community. In this context, it is important that healthcare professionals know about medicinal plants and their use in the community, as they can become mediators between popular and scientific knowledge.